Distal stent graft-induced new entry after TEVAR or FET: insights into a new disease from EuREC - Czerny, Martin; Eggebrecht, Holger; Rousseau, Herve; Mouroz, Paul Revel; Janosi, Rolf-Alexander; Lescan, Mario; Schlensak, Christian; Böckler, Dittmar; Ante, Marius; Weijde, Emma vdr; Heijmen, Robin; Eckstein, Hans Henning; et al. (The annals of thoracic surgery, 2020)
Background - The study sought to learn about incidence and reasons for distal stent graft-induced new entry (dSINE) after thoracic endovascular aortic repair (TEVAR) or after frozen elephant trunk (FET) implantation, and develop prevention algorithms. - Methods - In an analysis of an international multicenter registry (EuREC [European Registry of Endovascular Aortic Repair Complications] registry), we found 69 dSINE patients of 1430 (4.8%) TEVAR patients with type B aortic dissection and 6 dSINE patients of 100 (6%) patients after the FET procedure for aortic dissection with secondary morphological comparison. - Results - The underlying aortic pathology was acute type B aortic dissection in 33 (44%) patients, subacute or chronic type B aortic dissection in 34 (45%) patients, acute type A aortic dissection in 3 patients and remaining dissection after type A repair in 3 (8%) patients, and acute type B intramural hematoma in 2 (3%) patients. dSINE occurred in 4.4% of patients in the acute setting and in 4.9% of patients in the subacute or chronic setting after TEVAR. After the FET procedure, dSINE occurred in 5.3% of patients in the acute setting and in 6.5% of patients in the chronic setting. The interval between TEVAR or FET and the diagnosis of dSINE was 489 ± 681 days. Follow-up after dSINE was 1340 ± 1151 days, and 4 (5%) patients developed recurrence of dSINE. Morphological analysis between patients after TEVAR with and without dSINE showed a smaller true lumen diameter, a more accentuated oval true lumen morphology, and a higher degree of stent graft oversizing in patients who developed dSINE. - Conclusions - dSINE after TEVAR or FET is not rare and occurs with similar incidence after acute and chronic aortic dissection (early and late). Avoiding oversizing in the acute and chronic settings as well as carefully selecting patients for TEVAR in postdissection aneurysmal formation will aid in reducing the incidence of dSINE to a minimum.
Gesehen am 22.04.2021